Digitalization of the Sales System at Kios Mie Ayam Kangkung Subur, Cilegon City Using the Laravel Framework - Mansyuri, Umar; Hamdan, Hamdan; Armana, Ardan (PT Mattawang Mediatama Solution, 2025)
The rapid advancement of information and communication technology (ICT) has brought significant changes to various business sectors, including micro, small, and medium enterprises (MSMEs). However, many MSMEs still rely on manual systems that are prone to errors, inefficiencies, and difficulties in recording and analyzing transactions. This research aims to develop a digital sales information system for Kios Mie Ayam Kangkung Subur in Cilegon City using the Laravel framework. The system was designed using a Research and Development (R&D) approach and developed with the Laravel PHP framework and MySQL database, following the Model-View-Controller (MVC) architecture. Data collection methods included observation, interviews, and documentation study. The development process involved system requirement analysis, interface and database design, implementation, testing, and documentation. The final product is a web-based application that supports key functions such as login and authentication, menu management, transaction processing, receipt printing, and sales reporting. Black-box testing was conducted to evaluate the system’s functionality, and results showed that all modules performed according to expectations. The system proved to be user-friendly, efficient, and capable of improving transaction accuracy and operational speed. In conclusion, the developed digital sales system successfully meets the needs of Kios Mie Ayam Kangkung Subur and contributes to enhancing the kiosk’s business processes through automation. The system also lays the groundwork for future technology adoption, such as online ordering or mobile access. This study demonstrates that Laravel is an effective solution for MSMEs looking to transition into the digital era and streamline their business operations.